The use of brexpiprazole amongst individuals with insufficient outcomes with aripiprazole or bupropion: A case series. Issue 4 (10th February 2018) - Aladeen, Traci; Westphal, Erica; Lee, Yena; Rong, Carola; Rainka, Michelle; Capote, Horacio; McIntyre, Roger S.
Abstract: Purpose: We sought to characterize the clinical experience of outpatients treated with brexpiprazole after achieving suboptimal outcomes with aripiprazole or bupropion as determined by the treating psychiatric provider. Design and methods: Case series; inefficacy, intolerability, or other unsatisfactory outcome to previous trial with aripiprazole or bupropion. Findings: The majority of individuals in our sample exhibited tolerability of brexpiprazole. In addition, reduction in mean PHQ‐9 scores was observed with brexpiprazole treatment. Implications: The results of our preliminary analysis suggest that a subpopulation of adults who have insufficient outcomes on aripiprazole or bupropion due to intolerability, inefficacy or other unsatisfactory outcome may benefit by switching to brexpiprazole treatment. Larger randomized controlled trials are needed, as well as sophisticated network analysis to further understand efficacy and tolerability differences between atypical antipsychotics.